Reflexivity and ethical research practice while interviewing on sexual topics - Rodríguez-Dorans, Edgar (International journal of social research methodology, 2018)
Reflexivity is a multimodal research feature that relies on the researcher's subjectivity and self-awareness. This paper discusses uses of reflexivity when carrying out qualitative in-depth interviews on sexual topics. Through extracts of a challenging interview, where the challenge comes in the form of sexualised provocation from one man to another, this paper considers the benefits of using reflexivity to address emerging complexities in the interview process. The discussion focuses on ethical research practice through the lens of three forms of reflexivity: (1) reviewing the values that underpin a research project, with emphasis on the tension between rationality and intuition; (2) emotional self-awareness and self-care; and (3) recognition of the power dynamics in the researcher-participant relationship. Reflexivity promotes an intuition-informed decision-making process as a means to achieve ethical practice and conduct interviews with sensitivity and proficiency.